Dampak Penggunaan Teknologi dalam Manajemen Pembelajaran Pendidikan Islam Anak Usia Dini - Manora, Hecksa; Khasanah, Nevi Laila; Putri, Finna Nanda (Bouseik: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The rapid integration of technology in various educational fields, including Islamic Early Childhood Education (PIAUD), raises both opportunities and challenges. This research explores the impact of technology use in PIAUD learning management, focusing on teacher performance and student development. The aim of the study is to understand how technology influences teaching effectiveness and holistic child development while preserving Islamic values. Using a qualitative library research method, this study analyzed relevant literature from reputable sources. The findings reveal that technology, when used appropriately, enhances teacher efficiency, diversifies teaching methods, and enriches students' learning experiences. Technology can be a powerful tool to teach Islamic values in engaging ways, such as through interactive storytelling and educational applications. However, it also requires careful guidance from teachers and parents to maintain a balance between digital engagement and face-to-face social interaction, crucial for children's moral and spiritual growth. The research emphasizes the importance of a holistic and integrated approach, combining technology with traditional learning to ensure comprehensive child development. Teacher training programs are essential for effective technology management in PIAUD, and a collaborative framework between schools and families is recommended. The study highlights the need for balanced policies that support responsible technology use, prioritizing children's spiritual and character development.